1 Thessalonians 4:13 and grief management in Nigerian churches - Solomon O. Ademiluka (In die Skriflig)
1 Thessalonians 4:13 indicates that the Thessalonian Christians were deeply grieved about the death of their loved ones because they were not sure of the status of the deceased in the supposedly imminent parousia. Paul admonishes them not to grieve like those who have no hope, a caution which is highly relevant in Nigeria where death causes harrowing grief for those bereaved. This article interrogated the extent to which the application of this text relieves grief for Nigerian Christians, as well as its attendant impact on the people’s culture. The article employs the historical-critical exegesis and the phenomenological approach. It found that in the traditional African setting, the grieving process involved the performance of certain rituals which Christianity has condemned as heathen, as they contradict the injunction in 1 Thessalonians 4:13. Such mourning practices have been substituted with Christian models. Still, unfortunately, apart from being ineffective in addressing grief, this pastoral approach has impacted negatively on the cultural heritage and identity of Nigerian Christians. Therefore, for Christian burial in Nigeria to be desirable and effective in addressing mourners’ grief, there is a need for it to accommodate traditional practices as much as possible.